2017
DOI: 10.1161/circinterventions.116.004157
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic Control Status After Percutaneous Coronary Intervention and Long-Term Clinical Outcomes in Patients With Type 2 Diabetes Mellitus

Abstract: C ardiovascular disease is the major cause of mortality in patients with type 2 diabetes mellitus.1 Although intensive therapy to lower glucose has consistently been reported to reduce microvascular complications of type 2 diabetes mellitus, 2,3 whether intensive glycemic control reduces macrovascular complications and improves clinical outcomes remains controversial. 4,5 Limited data are available regarding the effect of intensive glycemic control for secondary prevention in patients with established cardiov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 27 publications
7
31
1
Order By: Relevance
“…Even though strict and multifactorial comprehensive management of atherosclerotic risk factors, such as obesity, smoking, lipid disorders and hypertension in secondary prevention of CV events in patients with diabetes is recommended [3], the prognostic implication of HbA1c level is still controversial and only a limited number of studies have addressed it with respect to CV mortality in patients with established coronary artery disease who underwent PCI. Moreover, most of previous studies binarized using 7.0% HbA1c and failed to show any significant differences in the incidences of adverse CV events between the groups [35][36][37][38][39][40], a finding which is consistent with that of this study. For a detailed evaluation of the prognostic impact of preprocedural HbA1c level, this study divided the participants into 5 groups with an almost equal distribution of patient numbers in each group, < 6.5%, 6.5-7.0%, 7.0-7.5%, 7.5-8.5% and ≥ 8.5%, allowing us to focus on the risk of lower HbA1c levels.…”
Section: Discussionsupporting
confidence: 91%
“…Even though strict and multifactorial comprehensive management of atherosclerotic risk factors, such as obesity, smoking, lipid disorders and hypertension in secondary prevention of CV events in patients with diabetes is recommended [3], the prognostic implication of HbA1c level is still controversial and only a limited number of studies have addressed it with respect to CV mortality in patients with established coronary artery disease who underwent PCI. Moreover, most of previous studies binarized using 7.0% HbA1c and failed to show any significant differences in the incidences of adverse CV events between the groups [35][36][37][38][39][40], a finding which is consistent with that of this study. For a detailed evaluation of the prognostic impact of preprocedural HbA1c level, this study divided the participants into 5 groups with an almost equal distribution of patient numbers in each group, < 6.5%, 6.5-7.0%, 7.0-7.5%, 7.5-8.5% and ≥ 8.5%, allowing us to focus on the risk of lower HbA1c levels.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, a post-trial study conducted by monitoring the UKPDS cohort for up to 10 years demonstrated the emergence of reductions in the risks of MI and death from any cause in the intensive therapy group 21 . Furthermore, a recent study of diabetic patients undergoing PCI showed that a HbA1c level <7.0% at 2 years was associated with a reduction in major cardiovascular events that was mainly attributed to revascularization 22 . However, only 20% of the patients had an AMI diagnosis at the time of the index PCI which limits the extension of the result to AMI patients.…”
Section: Discussionmentioning
confidence: 99%
“…Stroke. Ten studies reported on the incidence of stroke [24,26,29,31,[39][40][41][42][43][44]. The results of the meta-analysis showed that there was no significant difference in stroke incidence between diabetic patients with lower preoperative HbA1c levels and those with higher preoperative HbA1c levels after cardiac surgery (OR = 1:49, 95% CI 0.94-2.37, P = 0:37, and I 2 = 8%), as shown in Figure 4.…”
Section: Risk Of Biasmentioning
confidence: 99%